Liposomal Formulations: A Recent Update - Surendra S. Agrawal; Vrinda Baliga; Vaishali Y. Londhe (Pharmaceutics)
Liposome-based drug delivery technologies have showed potential in enhancing medication safety and efficacy. Innovative drug loading and release mechanisms highlighted in this review of next-generation liposomal formulations. Due to poor drug release kinetics and loading capacity, conventional liposomes have limited clinical use. Scientists have developed new liposomal carrier medication release control and encapsulation methods to address these limits. Drug encapsulation can be optimized by creating lipid compositions that match a drug’s charge and hydrophobicity. By selecting lipids and adding co-solvents or surfactants, scientists have increased drug loading in liposomal formulations while maintaining stability. Nanotechnology has also created multifunctional liposomes with triggered release and personalized drug delivery. Surface modification methods like PEGylation and ligand conjugation can direct liposomes to disease regions, improving therapeutic efficacy and reducing off-target effects. In addition to drug loading, researchers have focused on spatiotemporal modulation of liposomal carrier medication release. Stimuli-responsive liposomes release drugs in response to bodily signals. Liposomes can be pH- or temperature-sensitive. To improve therapeutic efficacy and reduce systemic toxicity, researchers added stimuli-responsive components to liposomal membranes to precisely control drug release kinetics. Advanced drug delivery technologies like magnetic targeting and ultrasound. Pro Drug, RNA Liposomes approach may improve liposomal medication administration. Magnetic targeting helps liposomes aggregate at illness sites and improves drug delivery, whereas ultrasound-mediated drug release facilitates on-demand release of encapsulated medicines. This review also covers recent preclinical and clinical research showing the therapeutic promise of next-generation liposomal formulations for cancer, infectious diseases, neurological disorders and inflammatory disorders. The transfer of these innovative liposomal formulations from lab to clinical practice involves key difficulties such scalability, manufacturing difficulty, and regulatory limits.